The Analisis Instalasi Sistem Plumbing Air Bersih pada Lantai III Gedung Rumah Sakit Umum Daerah Ruteng - Panggar, Alfonsus Zenelius; Koehuan, Verdy A.; Pell, Yeremias M. (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2024)
Research aims to analyze the clean water installation system in the Nursing Care Room on Floor III of the Ruteng Regional General Hospital building which is divided into three lines, namely the pump line to the upper reservoir, the reservoir line to distribution pipe A and the reservoir line to distribution pipe B. Installation system plumbing is an installation to meet the water needs of every plumbing equipment installed in a building. The analysis results show that the need for clean water in installation line A is 990 liters, while for installation line B it is 1,410 liters. So the total water requirement per day for the clean water plumbing system installation at Ruteng Regional Hospital is 2,400 liters per day. The pump power requirement is 170.45 Watts with a total head of 26.059 m and a flow rate of 2.41 m3/hour. If the analysis of pump needs is also to serve the clean water needs for the 1st and 2nd floors, assuming the water needs are the same as for the 3rd floor, each at 2.41 m3/hour with a total discharge of 7.23 m3/hour and a total pump head. 39.13 m, and the pump power requirement is 767.87 Watts.